A multidisciplinary approach to expand the use of pediatric ECLS systems in Turkey - Onan, İsmihan Selen; Haydın, Sertaç; Ündar, Akif; Yalindağ-Öztürk, M. Nilüfer; Demirkol, Demet; Kalkan, Gökhan; Ceyran, Hakan; Atay, Yüksel; Şaşmazel, Ahmet; Karaçi, Ali Rıza; Şevketo?lu, Esra; Köroğlu, Tolga Fikri; et al. (Wiley, 2015)
Extracorporeal life support (ECLS) systems were initially used in children after open heart surgery in 1972 and in neonates after meconium aspiration in 1975 (1,2). During the following years, this technology significantly improved, and the use of these systems rapidly increased worldwide. Venoarterial ECLS has been frequently used after open cardiac surgery, whereas venovenous ECLS is widely used in pediatric intensive care units (ICUs) (3). Less commonly, arteriovenous ECLS systems are used for the clearance of carbon dioxide from blood, and their use has been reported in Turkey (4). In the USA, it has been suggested that 2800 newborn patients benefit from ECLS systems in a year. Statistically, this represents 1/1309 of live births (5). The use of ECLS systems requires a multidisciplinary team approach with standard clinical programs to provide qualified and satisfactory patient care, rather than an individual effort (5,6).
Keywords: Turkey; Pediatric ECLS Systems; Multidisciplinary